Effects of drought and mycorrhiza on wheat and aphid infestation. Issue 19 (28th August 2020) - Pons, Caroline; Voß, Ann‐Cathrin; Schweiger, Rabea; Müller, Caroline
Abstract: The impacts of climate change on worldwide crop production become increasingly severe. Thus, sustainable enhancements of agricultural production are needed. The present study investigated the effects of drought and arbuscular mycorrhizal fungi on wheat plants ( Triticum aestivum ) and their interaction with aphids. Considering predicted climate change scenarios, wheat plants were exposed to well‐watered conditions, continuous drought (CD), or pulsed (PD) drought and plants were grown without (NM) or with mycorrhizal (AM) fungi. Ear biomass and harvest index were evaluated when grains were produced. Moreover, drought‐ and mycorrhiza‐induced changes in the amino acid composition of leaf phloem exudates were studied and the population growth and survival of Sitobion avenae aphids on those plants measured. Wheat plants responded differently toward the irrigation treatments. Under drought stress, ear biomass was reduced, while AM resulted in an enhanced harvest index. In phloem exudates especially, relative concentrations of the osmoprotectant proline were modulated by drought. Aphid population size was influenced by the interaction of drought and mycorrhiza treatment. This study emphasizes the pronounced influence of irrigation frequency on plant performance and indicates positive contributions of AM that may be relevant for agriculture. Abstract : Wheat plants were exposed to different irrigation regimes, and the effects of arbuscular mycorrhiza (AM) on plant and aphid performance were tested. For plants experiencing continuous or pulsed drought, AM had a growth‐promoting effect. Aphids had a poorer survival on those plants, indicating positive effects of AM in agriculture.